The Interaction Patterns Between Malay and Javanese Students in a Multicultural School Environment - Pirkun; Ari Irawan (JESS (Journal of Educational Social Studies), 2025)
In a multicultural society, interaction between ethnic groups plays a crucial role in maintaining social cohesion. Schools, as a small representation of a diverse culture, play a strategic role in fostering social harmony among students from diverse cultural backgrounds. This study aims to describe and analyze patterns of social interaction between Malay and Javanese students in a multicultural school environment, particularly in a transmigration area. The primary focus of the study is patterns of social interaction, the factors that influence them, and the role of schools in fostering cross-cultural social integration. The research approach used was a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving students, teachers, and the principal. The results indicate that interactions between Malay and Javanese students still tend to be structured along ethnic lines. This pattern reflects a tendency toward exclusivity in social interactions. Factors such as differences in language and cultural habits, unequal participation in school activities, and the uneven implementation of inclusive policies contribute to limited cross-cultural interaction. Thus, education is expected to function not only as a means of recognising diversity, but also as a vehicle for fostering social harmony in the school environment.